Pengaruh Tumbuhan Liar Berbunga terhadap Tanaman Tebu dan Keberadaan Parasitoid di Pertanaman Tebu Lahan Kering, Cinta Manis Sumatera Selatan - Dewi Meidalima (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Sugarcane is one of commodity plants that can grow well in dry land. Sugarcane plantation area at Cinta Manis is approximately 25,000 hectares. The purposes of this study were  to determine the effect of wild flowering plants on sugarcane and the presence of parasitoids.  This study was conducted in PTPN VII Cinta Manis  South Sumatra, from February to September 2012. The results indicated that wild flowering plants in Cinta Manis sugarcane plantations consisted of 28 families and 91 species. Observation and identification of wild  flowering  plants conducted on 1 ha plot obtained as many as 23 species, 8 of which are the most dominant species, namely Borreria alata, mitracarpus hirtus, Cyperus tunuiculmis, Cyperus plavipus, Richardia brasiliensis, Cleoma rutidosperma, Ageratum conyzoides, and  Spermacoce remota. The presence of wild flowering plants had no effect on weight, length, diameter and number of segments of sugarcane. Number of egg parasitoids of sugarcane pests found on land with and without the wild flowering plants as much as 1,489 and 1,508 pieces respectively. Number of parasitoids  larvae were found on the land with and without the wild flowering plants as much as 343 pieces and 234 pieces respectively.